CT-eKit: computational thinking interactive learning / Ong Sing Ling, Jill Ling and Fetylyana Nor Pazilah - Ong, Sing Ling; Jill, Ling; Pazilah, Fetylyana Nor (Universiti Teknologi MARA, Kedah, 2023)
With the spread of digital technologies, the learning trend and student preferences have changed drastically. Many learners now prefer to learn from a variety of online platforms. Students are more engaged with electronic gadgets in this ever-changing digital era. However, the majority of the existing online platforms do not cater to learning in an active environment and limit students’ participation, particularly in learning Computational Thinking (CT). Hence, this innovation aims to innovate a CTeKit, a collective teaching aid that emphasises Inquiry-based learning (IBL), developed to facilitate the learning process on the CT topic. The CT-eKit consists of three main activities: a CT video, a Kahoot CT quiz and a Scratch CT Concepts game to learn the four CT concepts: decompose, pattern, abstraction and algorithm in a fun and interactive environment. A mixed method was employed to investigate the students' learning experience with CT-eKit. This study involved 120 students from the Foundation in Science programme of the University of Technology Sarawak (UTS). Based on the results, CT-eKit is significant to be applied in the foundation computing course for the students as CT-eKit helps the students have a deeper understanding of the course, and they enjoy the fun learning. Policymakers and other stakeholders can incorporate or embed CT into the curricula. In addition, future work could look into the potential to commercialise the idea of CT-eKit as it is also one of the topics in the Malaysian Standard Secondary School Curriculum, Basic Computer Science or Asas Sains Komputer in Form 1 syllabus.